Keterampilan Memberikan Penguatan (Reinforcement) Pada Mata Pelajaran PAI di SMK Negeri 6 Bone - Nurhayati, R; Andra Ningsih, Diarti; P, Sudirman; Muh. Taufiq Nur, A; Kurnia, Sitti; Hidayah, Nur; Fitrawati, Nurul; Khairati, Mismaya (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2023)
Teaching skills are crucial in the student learning process and should be mastered by educators. The reinforcement aspect of applying teaching skills can be divided into two categories: verbal reinforcement, which includes words or phrases like "correct," "good," "well done," and so on, and nonverbal reinforcement, which involves facial expressions and body language such as smiles, nods, applause, thumbs up, and the like. Additionally, it is essential to understand the supporting and hindering factors that influence students' engagement in response to the reinforcement provided by teachers. The objective of this research is to describe how teachers employ reinforcement skills and the factors that support or hinder students' active participation in the learning process. This study employs a qualitative research approach with a descriptive analytical method. Data collection techniques include interviews and documentation, and data analysis involves using source, technique, and time triangulation. The research findings indicate the importance of understanding the skill of providing reinforcement in the context of Islamic Religious Education (PAI). Proficiency in providing reinforcement can enhance students' attention, stimulate their learning motivation, and help shape their behavior. However, some challenges include students' difficulty in grasping the subject matter, indifference towards assignments, and a lack of interest in learning.